2014
DOI: 10.1002/rcm.6969
|View full text |Cite
|
Sign up to set email alerts
|

An analytical approach to the forensic identification of different classes of new psychoactive substances (NPSs) in seized materials

Abstract: The identification of NPSs in confiscated materials was successfully achieved via GC/MS coupled with LC/HRMS and, in a few cases, NMR analyses. The availability of GC/MS libraries is of great assistance in the identification of new drugs. Alternatively, the study of characteristic molecule fragments combined with the determination of their accurate masses can be a useful approach to identify unknown samples not previously analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…The present analytical approach, based on the combination of the information obtained employing different analytical techniques, already adopted for the identification of unknown seized samples, allowed the identification of bk‐2‐CB in the seized material. bk‐2‐CB, to our knowledge, is not at the moment an explicitly controlled substance in any country, although in Italy it can be considered an analogue of cathinones and therefore scheduled.…”
Section: Resultsmentioning
confidence: 99%
“…The present analytical approach, based on the combination of the information obtained employing different analytical techniques, already adopted for the identification of unknown seized samples, allowed the identification of bk‐2‐CB in the seized material. bk‐2‐CB, to our knowledge, is not at the moment an explicitly controlled substance in any country, although in Italy it can be considered an analogue of cathinones and therefore scheduled.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the six compounds (UR-144, XLR-11, AKB-48, and AB-FUBINACA) have been identified in samples of synthetic cannabinoids obtained on the street (Kavanagh et al, 2013; Uchiyama et al, 2013; Strano Rossi et al, 2014). All six of the compounds have been found in blood or urine samples (or identified by verbal report) of users reporting adverse effects (Behonick et al, 2014; Gugelmann et al, 2014; Mohr et al, 2014; Strano Rossi et al, 2014), and the use of UR-144 or XLR-11 has been reported in cases of driving under the influence (Lemos, 2014; Musshoff et al, 2014). Of further concern, several of these compounds have been reported to produce significant adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…It does not appear that a formal study of the fragmentation mechanisms of cathinones, including ethylone, has been completed, however, the origins of many of the characteristic fragments have been proposed 40, 41, 42, 43, 44, 45, 46…”
Section: Resultsmentioning
confidence: 99%